Study on dry friction vibration model based on energy method. Issue 1 (5th January 2022) - Zhu, Fenglin; Jie, Fan Yu; bin, Li; Cheng, Xu Cheng
Abstract : Purpose: This study aims to establish the friction vibration model. Design/methodology/approach: The friction vibration experiment was carried out on a pin disk friction tester. The causes of friction vibration are discussed, and the friction vibration model is established based on the energy method. Findings: The experimental and simulation results show that the main cause of friction vibration is the nonlinear change of friction coefficient; degree of the friction vibration has a positive relationship with the friction relative velocity and normal contact positive pressure; the proposed friction vibration model is highly consistent in chaotic attractor and time-frequency distribution map and can well predict friction vibration. Originality/value: The proposed friction vibration model is highly consistent in chaotic attractor and time-frequency distribution map and can well predict friction vibration.